iS3-based digital twin system for engineering geological information along rock tunnel axis - Huaiyuan Sun; Yi Rui; Yiming Dai; Danjie Sheng; Mengqi Zhu; Xiaojun Li; Hehua Zhu (Tunnelling and Underground Space Technology, 2026)

A new species of Nilssoniopteris (Bennettitales) from the Lower Cretaceous Jianchang Basin, western Liaoning, NE China - Yue Wang; Xiao Tan; Jiayi Zhang; Rui He; Mengyang Zhang; Fei Liang; Yunfeng Li; Chunlin Sun (Review of Palaeobotany and Palynology, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

In situ sludge reduction induced by graphene oxide: Mechanistic insights into metabolic uncoupling, maintenance energy and cryptic growth - Yaodong Wu; Yiqi Sun; Rui Yu; Yanan Cui; Fan Yang; Jun Li; Zehao Zhang (Bioresource Technology, 2026)

Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

pH regulation of 1,2-bis(trimethoxysilyl)ethane hydrolysis pathways for enhanced wet state stability of TEMPO-oxidized cellulose nanofiber aerogels - Aojia Zhang; Rui Teng; Quan Zhang; Xue Liu; Biyao Sun; Chengcheng Suo; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Selective flotation of lepidolite from albite and quartz using a Hyperbranched surfactant THQ-8: Insights through foam property and adsorption behavior - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Balancing fermentation control and aroma complexity in semi-spontaneous kiwifruit fermentation through Saccharomyces cerevisiae inoculum level - Wanju Yan; Yuanjing Li; Zitong Zhang; Rou Cai; Sinuo Feng; Jia Han; Wangsheng Sun; Rui Cai; Zhouli Wang; Jing Guo (Food Research International, 2026)

Joint hierarchical Bayesian modeling of tree height and height to crown base in Chinese fir plantations using SHAP-guided variable selection - Baoying Wang; Rui Li; Yujun Sun (Forest Ecology and Management, 2026)

Continuous versus discontinuous biodegradable film mulching in maize: A five-year field study on soil carbon sequestration, productivity, and microplastic legacy - Kai Wang; Xiao Li; Shiyan Sun; Gary Y. Gan; Ying Zhao; Qiang Li; Jiangxin Gu; Rui Jiang (Field Crops Research, 2026)

Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

Breath figure-derived Janus membrane with CCM/PNIPAM hydrogel layer for highly efficient salt-tolerant evaporation - Ruiyun Cai; Hanxue Sun; Rui Jiao; Zhaoqi Zhu; Jiyan Li; An Li (Desalination, 2026)

Study on dynamic response and damage mechanism of tunnel across reverse fault based on different earthquake action modes - Rui Sun; Xiaojun Li; Yanping Yang; Ren Deng; Teng Li; Dingding Xiong (Tunnelling and Underground Space Technology, 2026)

Flotation of quartz from albite using oligomeric surfactant THQ-8 in synergy with NaOL - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Research on the application of metal oxides in flue gas mercury removal enabled by machine learning - Yang Sun; Miao An; Rui He; Cui Jie; Jiaoyu Yang; Mi Liu; Zhiling Qian; Jing Yin; Yanxiao Cao; Hongcheng Ruan; Honghu Li (Journal of Environmental Chemical Engineering, 2026)

Identifying global key regions where vapor pressure deficit dominates drought intensification - Yuxin Miao; Dehong Si; Zhijie Zheng; Yani Gun; Rui Li; Wanting Li; Wenzhang Sun; Dongfei Yang; Yaxin Li; Xinyue Wang; Guofeng Zhu (Global and Planetary Change, 2026)

Revolutionizing coal seam gas extraction with electrohydraulic discharge: A sustainable path forward - Fei Ren; Rui Li; Zhaobiao Yang; Beilei Sun (Gas Science and Engineering, 2026)

Isolation and characterization of broad-host-range bacteriophages and their alleviation of liver and kidney injury in a mouse model of S. aureus infection - Xinyan Yao; Linlin Huang; Chaoxiang Jia; Dai Peng; Rui Cao; Xiangshun Sun; Yingqian Han; Yang Liu; Yanbin Yang; Guoyu Yang; Yueying Wang; Heping Li (Food Research International, 2026)

Pectin-driven microphase separation regulates hierarchical network formation and rheological functionality in egg yolk high-density lipoprotein fibril hydrogels - Jian Li; Xinyi Ju; Rui Chuang; Zihe Ding; Huajiang Zhang; Lina Xu; Jing Sun; Hanyu Li; Tong Zhang; He Zhang (Food Chemistry, 2026)

Dual signal-enhanced immunochromatographic test strip based on Au@PtNPs: From sensitive detection of thiamethoxam to multiplex pesticide screening in vegetables - Zhengtao Li; Lingjun Geng; Jiashuai Sun; Jingcheng Huang; Rui Xu; Zhen Guo; Shouyi Dou; Liying Zhang; Fangling Du; Yemin Guo; Xia Sun; Nortoji A. Khujamshukurov (Food Chemistry, 2026)

Differential regulation of exercise fatigue by Spirulina peptides: energy metabolism and antioxidant defense mechanisms mediated in a comparative swimming model - Tao Ding; Zhaoxin Li; Rui Duan; Junjie Zhang; Lihong Xing; Xiaojie Sun; Fang Zhang; Qingyan Wang; Shuo Qie; Yi Yang; Cuiping Song (Food Chemistry, 2026)

Maternal exposure to particulate matter during pregnancy and offspring liver function - Ziyi Zhou; Bin Sun; Yudiyang Ma; Ning Chen; Haibo Li; Wenpu Shao; Rui Tang; Lei Zheng; Meiqi Xing; Xinru Zhao; Yibing Zhu; Yaohua Tian (Environmental Pollution, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Modeling global atmospheric antimony (Sb) concentrations and depositions over the past two decades - Wenwen Sun; Zheng Li; Rui Li (Environmental Pollution, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Multifunctional thermally regulated aerogels for efficient solar-driven evaporation and thermoelectric power generation - Cheng Niu; Haizhen Xue; Hanxue Sun; Jiyan Li; Zhaoqi Zhu; Weidong Liang; Rui Jiao; An Li (Chemical Engineering Journal, 2026)

Multi-pathway environmental and health impacts of volatile compound emissions from waste-to-energy plants in China - Guiying You; Hefan Liu; Xiaoya Dou; Rui Sun; Jing Li; Shaodong Xie (Atmospheric Environment, 2026)

Soil deposition reduces bacterial network complexity and stability by shifts in life-history strategies on the Loess Plateau of China - Yanqing Guo; Hailun Zhang; Shunxiang Yao; Bin Zhu; Rui Ma; Xiuling Li; Qianjin Liu; Qiqi Sun; Shengli Guo; Yaxian Hu; Lanlan Du (Applied Soil Ecology, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Regulatory mechanisms underlying dynamic variation of DHA, EPA, and odd-chain fatty acids content in Auran tiochytrium sp. SZ13 - Rui Luo; Buwen Sun; Jiaxing Li; Nannan Zhang; Meihan Chen; Ziyu Du; Shuo Li; Jialin Guo; Bin Liu; Dongzhe Sun (Algal Research, 2026)

Can unmanned aerial vehicle laser scanning serve as an effective alternative to traditional field methods for predicting tree growth in even-aged Chinese fir (Cunninghamia lanceolata) plantations? - Rui Li; Baoying Wang; Ruiting Liang; Zhidan Ding; Zhaoting Zhu; Yujun Sun (European Journal of Forest Research, 2026)

Genesis of the Jiawula Pb–Zn–Ag deposit in the Great Xing’an Range, NE China: constraints from fluid inclusions and S–Pb isotopes - Hongzhe Xie; Guiyuan Sun; Quzong Baima; Xinyu Gao; Ziwen Yang; Rui Tian; Lin Yang; Licheng Zhao; Zhiping Li (Journal of Asian Earth Sciences, 2026)

Binocular-depth-guided dual-view camera-LiDAR fusion for kiwifruit pose estimation in robotic harvesting - Shiao Niu; Leilei He; Qilin Gong; Qichen Huang; Ruichao Luo; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Anastasia Grecheneva; et al. (Computers and Electronics in Agriculture, 2026)

Bone biochar as a bifunctional catalyst for sustainable co-removal of nitrate and phosphate in constructed wetlands - Tao Liu; Hao Qin; Sihan Li; Gongliang Zhang; Rui Wang; Yi Sun; Haihua Wu; Yuxin Zeng; Yi Chen (Water Research, 2026)

Freeze-thaw damage evolution and crack propagation failure mechanism of red sandstone under non-uniform water distribution conditions - Li Wenbo; Sun Jielong; Chen Rui; Wang Yu; Wen Ziyi; Lou Bing (Transportation Geotechnics, 2026)

Exploring the cooling effects of park green spaces and their influencing factors from the perspective of urban-rural gradient - Yingying Li; Yulin Bian; Rui Zhou; Tong Sun; Shujun Zhang; Jinzhuo Zhao; Chun Wang; Jianan Wang (Sustainable Cities and Society, 2026)

Ailanthone exerts insecticidal activity as a non-orthosteric 20E antagonist by promoting ecdysone receptor degradation - Bingbing Li; Xinyu Gao; Rui Sun; Qianyu He (Pesticide Biochemistry and Physiology, 2026)

Heterologous expression of Arabidopsis RLP30 enhances fungal resistance in poplar - Lijuan Zhao; Qiang Cheng; Xiaodie Huo; Conghui Li; Bingqing Li; Xueqin Meng; Qi Li; Rui Sun; ZeYao Li; Haitao Liu (Physiological and Molecular Plant Pathology, 2026)

Novel attenuating intestinal oxidative stress strategy: Selenium nanoparticles combined with curcumin impeding the endoplasmic reticulum stress & apoptotic pathways - Ze-yuan Sun; Ling Lu; Si-nian Li; Rui-chao Li; Ling-qing Kong; Ru-nan Zuo (PharmaNutrition, 2026)

Environmentally relevant imidacloprid exposure elicits hippocampal microglial apoptosis via JNK-FOXO3 pathway: Implication for latent central neurotoxicity - Xinyi Wen; Meiyan Li; Zhongyuan Zhang; Jingwen Wang; Hao Hu; Weihong Wang; Jing Jin; Kairong Wang; Jian Sun; Rui Zhang (Journal of Hazardous Materials, 2026)

Elucidation of a novel skatole degradation pathway and key genes in Rhodococcus rhodochrous S3 - Kaihua Pan; Rui Fan; Qi Xie; Yike Lyu; Bingjie Xu; Qian Zhu; Mingliang Zhang; Qian Li; Weihao Zhu; Yanni Huang; Qing Hong; Lina Sun (Journal of Hazardous Materials, 2026)

A simple osmotic intervention suppresses nanoparticle-induced bacterial persistence during environmental disinfection - Rui Sun; Yijin Tian; Siyang Xue; Yueting Cui; Yunchen Zhao; Shuaishuai Li; Jiawei Yuan; Xuanxuan Zhang; Chengdong Zhang (Journal of Hazardous Materials, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

Multi-scale characterization of VOCs and CO2 emissions from the coking industry: an updated source profile and co-control framework - Guiying You; Sihua Lu; Rui Sun; Jiaxin Wei; Jing Li; Shaodong Xie (Environmental Research, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

Microwave-assisted synthesis of FeN Co-doped ZIF-8 derived carbon for low-concentration lithium recovery via CDI: Adsorption performance and mechanism - Yongsi Xie; Jiemei Fu; Chunxue Li; Juan Luo; Rui Ma; Shichang Sun (Desalination, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

A novel physics-driven remeshing technique for particle finite element method - Wen-Rui Sun; Ke-Jian Wang; Wen-Qi Guan; Xue Li; Wei Zhang; Wei-Hai Yuan (Computers and Geotechnics, 2026)

High-throughput prediction of the lowest triplet excitation energies in organic photovoltaic acceptors using physics-guided excess-factor-corrected fragment descriptors - Lei Cheng; Rui-Cheng Qin; Peng Xie; Ming-Yang Li; Yue Ren; Guang-Yan Sun (Chemical Engineering Journal, 2026)

Oxygen-vacancy-driven dipole ordering and anion anchoring in BaTiO3 nanofibers for high-performance gel polymer electrolytes in high-voltage lithium metal batteries - Yaoxiang Shan; Cong Kang; Bingkun Zang; Ting Li; Bingjia Lu; Rui Sun; Huiying Qu; Xucai Yin; Yang Ren (Chemical Engineering Journal, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Unraveling the spatial paradox of multi-hazard mitigation: divergent impacts of urban form and function on heat and pluvial flood hazards - Bomeng Wu; Rui Sun; Zhaoren Wang; Ye Tian; Lanyu Qin; Hezi Bai; Mengyuan Chen; Huocheng Lin; Shuang Li; Shuanning Zheng (Natural Hazards, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

Urbanization amplifies compound day-night heatwaves in the Yangtze River Delta urban agglomeration: Spatiotemporal characteristics and atmospheric drivers - Shiyao Li; Shifang Yu; Rui Yao; Peng Sun; Yi Liu (Urban Climate, 2026)

Inhalable HUCMSC-Lipo biomimetic formulation inhibits fibroblast activation in mouse and non-human primate pulmonary fibrosis models - Fangyu Zhao; Yige Sun; Haoran Wang; Dayong Hou; Rui Zhang; Wenjing Xia; Yongchen Zhang; Luyao Li; Xueqi Zhao; Kaiqi Wang; Wenwen Pan; Jiannan Wang; et al. (Science Bulletin, 2026)

Quantitatively linking karst groundwater quality to hierarchical recharge via uncertainty-aware Bayesian coupling - Changsuo Li; Zhenjie Zhang; Xiancang Wu; Tao Hu; Shasha Wu; Shuai Gao; Chunwei Liu; Bin Sun; Jiutan Liu; Rui Liu (Journal of Hydrology, 2026)

CWN-Net: a precise segmentation model for composite water networks using multi-source and multi-temporal remote sensing imagery - Mingyang Li; Huimin Lei; Fulin Li; Jiwen Huang; Yuzhi Shi; Shangjie Xu; Han Wang; Sinan Wang; Rui Wang; Lili Liu; Suzhen Cheng; Lei Guo; et al. (Journal of Hydrology, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Process-resolved characterization and multi-metric co-control of VOC emissions in pesticide manufacturing - Guiying You; Sihua Lu; Rui Sun; Jiaxin Wei; Jing Li; Shaodong Xie (Journal of Hazardous Materials, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Quinoa bran polyphenol extract ameliorates NAFLD through modulating Allobaculum and regulating pantothenate and CoA biosynthesis alongside retinol metabolism - Minjun Sun; Sarina Ma; Rui Wang; Ying Miao; Rui Huo; Qixin Gu; Wenhui Guo; Dongyan Li; Meili Zhang (Food Bioscience, 2026)

Unveiling the impact of mixed-strain solid-state fermentation on wheat bran dietary fiber: gluten protein structure evolution, dough rheological modulation and steamed bread quality enhancement - Xinhao Li; Rui Huang; Mengyuan Li; Lingfang Zhang; Xiaojie Qian; Binghua Sun; Sen Ma; Li Li (Food Hydrocolloids, 2026)

Enriched numerical manifold method with closed-form solutions for the crack-tip singularity in elastic fracture - Hua-rui ZHU; Hong ZHANG; Xi-long LI; Wei WU; Sun-jun HU; Gen-hua SHI (Computers and Geotechnics, 2026)

A Process-based classification of meteorological mechanisms influencing airborne pollen concentrations in northern and northwestern China - Zining Yuan; Huiyu Ning; Xingqin An; Qingyu Wei; Defang Wei; Wenqiao Xue; Ning He; Lina Di; Xinli Yang; Ying Li; Rui Li; Hongjian Li; et al. (Atmospheric Research, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

A novel LSTM-Kriging model for spatiotemporal interpolation of air pollution - Rui Xu; Jiaming Zou; Yuanfeng Sun; Jian Li; Liyi Guo; Shiming Shen; Hang Wan (Air Quality, Atmosphere & Health, 2026)

Identification of potential mechanisms of quercetin in diabetic peripheral neuropathy through integrated network pharmacology and experimental validation - Zanpeng Chen; Ziyu Li; Xiaowei Xue; Wei Song; Rui Zhang; Chao Wang; Bin Yan; Qing Sun; Qunli Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Non-nitrogen-fixing halophytes alleviate nitrogen limitation and decrease soil salinity through nitrogen transfer from nitrogen-fixing plants - Zehao Zhang; Tian Li; Yao Zhang; Rui Hu; Jiabao Li; Hongxiang Jin; Ying Fang; Zhaohua Lu; Jingkuan Sun (Plant and Soil, 2026)

Prevotella copri impairs bone mass via osteoclast activation in mice - Rui Li; Haiyan Zhang; Shiyong Xin; Tiantian Zeng; Wenchu Qian; Yawen Sun; Yunfei Cao; Yuxin Wang; Bin Li; Ming Tian; Hai Lin; Haifang Li (Molecular and Cellular Biochemistry, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

A nationwide analysis of hospitalised patients with lower respiratory infections in China: life-stage-specific pathogen spectra, co-detection networks, and sex disparities - Yamin Sun; Min Wang; Tian Qin; Jue Liu; Jiale Yuan; Pei Li; Xinchang Lun; Zhigang Wang; Linghang Wang; Rui Song; Xi Wang; Ronghua Jin; et al. (Science Bulletin, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Characteristics of VOCs and sulfur-containing compounds: Environmental and health implications in odor complaint hotspots of Chengdu, China - Guiying You; Liqiu Huang; Hefan Liu; Xiaoya Dou; Rui Sun; Jiaxin Wei; Jing Li (Journal of Environmental Sciences, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Uncovering the climate vulnerability of China’s poverty alleviation frontiers - Feng Zhao; Lijun Zuo; Yuyu Zhou; Liangzhi You; Huabing Huang; Rui Sun; Yuanyuan Zhao; Xunhuan Li; Dawei Zhang; Ran Meng (Global Environmental Change, 2026)

Unraveling the flame morphology and evolution in pulverized coal MILD combustion transition: experiments and theoretical analysis - Yongxin Chen; Tao Ren; Pu Liu; Zihao Guo; Jiangbo Peng; Xiaohui Li; Song Cheng; Rui Sun (Fuel, 2026)

Melatonin treatment improves chilling tolerance and maintains quality of postharvest Actinidia arguta fruit by regulating membrane lipid metabolism - Rui Wu; Xinqi Liu; Feiyang Wang; Shiwei Li; Baodong Wei; Qian Zhou; Yang Sun; Shunchang Cheng (Food Chemistry, 2026)

Effects of heat input on heat-affected zone of simultaneously welded cruciform fillet joints in Q550D and Q690D steels - Yize Gao; Xiao-Ling Zhao; Yan-Bo Wang; Rui Yan; Zhe Sun; Guo-Qiang Li (Engineering Structures, 2026)

Polyvinylpyrrolidone-enhanced terahertz metamaterials for room-temperature, trace VOC detection and discrimination - Rui Zhang; Lanju Liang; Xin Yan; Guifang Wu; Haiyun Yao; Zhenhua Li; Xiaofei Hu; Ziqun Wang; Zhaoqing Sun; Jie Huang (Chemical Engineering Journal, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

GPx6 downregulation drives ferroptosis in Kashin-Beck disease chondrocytes via the SLC7A11/GPx4 axis - Yinan Liu; Jie Li; Meng Zhang; Ying Zhang; Mengying Wang; Rui Wang; Xiaoming Zhao; Pinglin Yang; Jinghong Chen; Jian Sun (Apoptosis, 2026)

Enhanced deep nitrogen removal from low C/N wastewater via manganese-catalyzed iron-carbon micro-electrolysis coupled biological system: performance, mechanism, and microbial adaptability - Hengyuan Liu; Kai Wang; Feng Sha; Haibing Che; Rui Sun; Xiuhua Li (World Journal of Microbiology and Biotechnology, 2026)

Stress Interference between Multi-radial Boreholes During Hydraulic Fracturing in Multilayered Reservoirs Based on the Discrete Lattice Method - Tengda Long; Xiaoguang Wu; Yazhou Shen; Zixiao Xie; Zhongwei Huang; Gensheng Li; Rui Yang; Zhaowei Sun; Tao Pan; Naikun Hu; Xiaohua Wang (Rock Mechanics and Rock Engineering, 2026)

Bioaerosol multi-pollutant source localization in urban microclimates using an improved particle swarm optimization method with restricted search capabilities - Zhijian Liu; Yixiang Ma; Chenxing Hu; Haiyang Liu; Hongliang Zhang; Xin Li; Zhenhai Sun; Rui Rong; Zhijian Dong; Xiang Zhao; Guangpeng Yao (Sustainable Cities and Society, 2026)

Luminescent hydrogel-enabled electrochemiluminescent aptasensor and portable analyzer for on-site quantification of acetamiprid in vegetables - Jiashuai Sun; Lingjun Geng; Jingcheng Huang; Zhen Guo; Rui Xu; Zhiping Yu; Zhengtao Li; Peisen Li; Pengwei Zhang; Shengkun Ren; Elena Zavyalova; Yemin Guo; et al. (Journal of Hazardous Materials, 2026)

Nitrated apricot shell carbon catalyzes ketalization: Unraveling the reaction mechanism and pathways - Dongliang Duan; Guangxue Yang; Zhengping Dong; Rui Feng; Chuang Zhu; Yuxuan Li; BoYang Sun; Hongwei Zhao; Huanye Zhong (Journal of Environmental Chemical Engineering, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Highly efficient detection of imidacloprid in agricultural samples based on ZIF-8-derived carbon particles-modulated fluorescence polarization immunoassay - Rui Sun; Pei Lv; Bingqing Shen; Qian Wu; Yuan Xue; Lin Chen; Weibin Li; Zhenjiang Liu (Food Chemistry, 2026)

Who peaks, and why? City-level residential building carbon emission peaking patterns and driving mechanisms in China - Yanhui Yu; Rui Li; Shicong Zhang; Chanyuan Li; Haitong Zhe Sun; Weiguang Cai (Environmental Impact Assessment Review, 2026)

Hydrophobization engineering in nitrile hydratase-nicotinamidase cascade system: Promoting multi-tunnel formation for enhanced niacin biosynthesis - Yinbiao Xu; Rui Wang; Chaofan Li; Yu Liu; Xinyue Zhang; Hao Fu; Zongda Chen; Pei Zhou; Yang Sun; Hua Li; Yupeng Liu (Chemical Engineering Journal, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Arid–period floods and human adaptation promoted agricultural prosperity in the Neolithic heartland of the Middle Yellow River - Mengjing Li; Lin Chen; Yongxiu Lu; Rui Yang; Zili Wang; Huiling Sun; Aifeng Zhou (CATENA, 2026)

The application and uncertainty of the observation-based model in ozone and secondary aerosols simulation: A review - Jiaxin Wei; Rui Sun; Guiying You; Jing Li; Shaodong Xie (Atmospheric Environment, 2026)

Research on Dynamic Control of Flood Control Level for Jinxia Reservoir Group Considering Risks - Min Li; Yue Sun; Rui Feng; Wei Ding; Qianning Wang; Jinnan Zhang; Yong Peng; Feilin Zhu (Water Resources Management, 2026)

Green conversion of coal gangue acid leaching residue into a K2Si4O9 fertilizer material: a sustainable strategy for solid waste upcycling - Junli Zhang; Zhumei Sun; Yucen Gao; Ying Li; Rui Ma; Yanfang Chai; Haifang Wang (Waste Disposal & Sustainable Energy, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Superabsorbent and antimicrobial cryogel pads based on gelatin, sodium alginate and zinc oxide nanoparticles: Preparation, characterization and enhanced preservation of aquatic products - Jiaxuan Fang; Siyu Wu; Xiali Zeng; Rui Li; Zhenting Huo; Zhongjie Yu; Qingbao Ma; Di Sun; Yu Liu; Wei Jiang (Food Research International, 2026)

Biochar-driven cycling of Fe(II)/Fe(III) and Co(II)/Co(III) in cobalt ferrite for efficient norfloxacin degradation via Fenton-like pathway - Rui Gan; Fanguang Kong; Xiao Zhao; Daoqing Liu; Shuo Zhang; Wen Liu; Si Li; Weiling Sun (Chemical Engineering Journal, 2026)

Perfusion process-oriented metabolic engineering enhances 1,3-dihydroxyacetone production efficiency in Gluconobacter thailandicus - Yang Sun; Zilong Hu; Yuwei Shan; Rui Wang; Tang Liu; Kuiqi Jin; Qingxuan Miao; Cheng Ye; Jianqi Nie; Daiyin Zuo; Yinbiao Xu; Hua Li; et al. (Chemical Engineering Journal, 2026)

Responses of soil nitrogen mineralization to ecological restoration-oriented constructed grasslands with different recovery ages in the Three-River Headwaters Region - Jie Zhu; Baolin Li; Guoyi Zhou; Yecheng Yuan; Wei Liu; Rui Li; Qiuyuan Tan; Qingling Sun (Plant and Soil, 2026)

Analysis of the species distribution and drug resistance of pathogenic microorganisms causing diabetic foot infections in Southwest China from 2020 to 2024: a retrospective cross-sectional analysis - Shangyu Zhang; Junchi Chen; Rui Sun; Yu Pan; Yusen Zhuo; Li Tang; Jianhua Zhu; Shuyang Li; Lin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Molecular Basis of Biostimulant-enhanced Recovery from Late-spring Frost in Vitis Vinifera: A Transcriptomic Dissection - Chaoyue Feng; Xi Chen; Xinyi Luo; Huiyu Zhu; Huiling Ma; Xiaojun Liu; Yulong Li; Quan Sun; Rui Wang; Yaqi Wang (Journal of Plant Growth Regulation, 2026)

What are the driving factors and spatial-temporal characteristics of the landscape ecological risk of the Yellow River Delta? - Yao Zhang; Rui Hu; Tian Li; Zehao Zhang; Zhanyong Fu; Kaikai Dong; Jinzhao Ma; Zhaohua Lu; Jingkuan Sun (Environment, Development and Sustainability, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Forecast of photovoltaic material recycling and assessment of supply-demand gaps considering recycling feedback and subsidies - Rui Zhang; Xiaowei Ma; Qingyu Sun; Chuandong Li; Yu Zhong (Waste Management, 2026)

Integrating carbon-based nutrient fertilization for urban soil management: Impacts on plant growth and microbial communities - Xihui Sun; Hong Liu; Rui Yu; Song Li; Xuemiao Tian; Huiwen Zhang; Lixin Niu; Yanlong Zhang (Urban Forestry & Urban Greening, 2026)

Rethinking the context dependent effects of factors on connecting transport choice at high-speed rail station: Evidence from two cross-sectional surveys during and after COVID-19 pandemic - Zhiyuan Sun; Rui Sun; Zehao Wang; Pengpeng Jiao; Yunxuan Li; Jianyu Wang; Huapu Lu (Travel Behaviour and Society, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A synergistic strategy to overcome temperature and concentration polarization in a joule-heating CNT/PTFE membrane distillation: From membrane preparation to process mathematic simulation - Tiantian Xu; Longji Li; Xiaojia Li; Liang Feng; Siyu Chen; Yang Xu; Yan Li; Zhiqing Luo; Zhirui Chen; Hongyi Li; Rui Wang; Feiyun Sun (Desalination, 2026)

Sustainable and selective gold extraction from electronic waste using conjugated microporous polymer aerogels - Wei Liu; Zhaoqi Zhu; Xicheng Liu; Mengqi Zhao; Rui Jiao; Peng Mu; Hanxue Sun; An Li (Chemical Engineering Journal, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

A wave-coupled movable bottom friction scheme for spectral wave modeling based on sediment grain size and ripple evolution - Xianghui Dong; Qingxiang Liu; Grant A. Smith; Ian R. Young; Huy Quang Tran; Rui Li; Jian Sun; Kejian Wu; Alexander V. Babanin (Coastal Engineering, 2026)

Synergistic in-situ structural modification and interfacial engineering of lignin toward multifunctional biodegradable films - Rui Gao; Zekai Jin; Lidong Li; Chenhuan Lai; Xueni Sun; Fuxiang Chu; Yupeng Liu; Shishuai Gao; Daihui Zhang (Bioresource Technology, 2026)

Exploring factors influencing the height growth of Cunninghamia lanceolata based on bootstrap bayesian network and random forest - Baoying Wang; Rui Li; Yujun Sun; Ruiting Liang; Zhaoting Zhu (Trees, 2026)

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Cottonseed protein as a sustainable alternative plant protein: Basic characteristics, recent advancements, applications and limitations - Xinjie Shang; Shu Li; Shiyu Lin; Shihao Sun; Li Liang; Yuyu Zhang; Rui Yang (Trends in Food Science & Technology, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Transmission and migration of antibiotic resistance genes following agricultural fertilization in sloping croplands - Yifei Sun; Rui Chen; Sarah van den Broek; Jiong Wen; Yuxiang Li; Xibai Zeng; Shiming Su; Gina Garland (Journal of Hazardous Materials, 2026)

Four decades of Landsat data reveal the evolution of nitrogen and phosphorus components driven by human activities in the northern South China Sea - Di Tian; Xinfeng Zhao; Xingxian Li; Lei Gao; Zuobing Liang; Rui Li; Shaoheng Li; Zaizhi Yang; Chengxiang Sun; Jianyao Chen (Journal of Environmental Management, 2026)

Explosive PM2.5 growth and health effects during extreme haze in Shanghai, China: Insights from surface and vertical observations - Wenwen Sun; Yang Chen; Shunyao Wang; Shenghua Zhang; Yuxin Zhang; Rui Li; Jialiang Feng; Jianyu Chen; Tiantao Cheng (Journal of Environmental Sciences, 2026)

Evaluating the environmental impact of hydrothermal cracking solid organic fertilizer: Carbon and nitrogen retention and toxic metals analysis - Rui Xia; Xiao-xiao Yang; Jue Wang; Kai-le Li; Zhi-peng Sun; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Journal of Environmental Sciences, 2026)

Thermal versus chemical effects of CO2 dilution on micro-mixing flame and NO emission - Dengke Chen; Chang Xing; Rongze Ma; Penghua Qiu; Yijun Zhao; Jingyu Guan; Rui Sun; Linyao Zhang; Li Liu; Zhen Cao (Fuel, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Synergistic control of Pseudomonas aeruginosa by LAB and phage for sustainable aquatic preservation - Siming Xue; Kairui Zhao; Rui Dong; Haichen Li; Ruizi Wang; Wei Cheng; Yuqi Fan; Qin Zhang; Ziyi Xue; Yujin Wu; Jun Zhang; Yanmei Sun; et al. (Food Bioscience, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Potential re-release of Co2+ by using Ceratophyllum demersum L as bioreactors to construct dual-converted Co9S8&Co2P for lithium-ion batteries - Huanzhong Zeng; Rui Liu; Yuanyou Peng; Jiyi Sun; Junlong Chen; Jinling Li; Jianzhou Niu; Fuliang Zhu; Fen Ran (Chemical Engineering Journal, 2026)

H₂-rich syngas from synergistic steam gasification of biomass with spent LIB cathodes: Catalytic kinetics and metal recovery - Ran Jiao; Lijie Sun; Bowen Li; Xinran Zhou; Yifei Xu; Yu Chen; Fenglei Qi; Xiaohao Liu; Rui Diao; Zhenting Zha; Peiyong Ma (Chemical Engineering Journal, 2026)

Fabrication of a pH-responsive nanodelivery platform based on ZnO and kasugamycin for synergistic delivery in the efficient and green management of rice bacterial leaf streak - Shaoyang Sun; Xiang Li; Ziyi Wu; Ze Lv; Yingjian Ma; Rui Zhao; Xinyu Guo; Jianguo Feng; Xuemin Wu; Yong Xu (Chemical Engineering Journal, 2026)

Dendritic mesoporous silica-confined phase-change composites in a sodium alginate aerogel for stable solar-driven water evaporation and energy harvesting - Cheng Niu; Yanju Jing; Rui Jiao; Zhaoqi Zhu; Hanxue Sun; Weidong Liang; Jiyan Li; An Li (Chemical Engineering Journal, 2026)

Selenium-Enriched Akkermansia muciniphila: A Novel Probiotic Bacterium for Se Supplementation - Wen Rui; Yuhang Sun; Xiaoqian Li; Jingpeng Yang; Xuna Tang (Probiotics and Antimicrobial Proteins, 2026)

Nitrogen-fixing bacteria and arbuscular mycorrhizal fungi alleviated nitrogen limitation in halophytes and reduced soil salinity in salt-aggregating and salt-secreting plants - Zehao Zhang; Tian Li; Rui Hu; Zhanyong Fu; Yao Zhang; Jinzhao Ma; Ping Wang; Jingkuan Sun (Plant and Soil, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

Corrigendum to “Silica nanoparticles induce cardiac injury and dysfunction via ROS/Ca2+/CaMKII signaling” [Sci. Total Environ., 837 (2022), 155733] - Yi Qi; Hailin Xu; Xueyan Li; Xinying Zhao; Yan Li; Xianqing Zhou; Rui Chen; Yanbo Li; Zhiwei Sun; Caixia Guo (Science of The Total Environment, 2026)

The wave-induced heat transport in the global ocean - Rui Li; Kejian Wu; Qingxiang Liu; Jin Liu; Shang-Min Long; Jian Sun; Alexander V. Babanin (Ocean Modelling, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Study on the irradiation control of urease activity and its solidification of red clay to enhance radon reduction - Yuanyuan Tang; Rui Liang; Jia Wei; Yiqing Sun; Weihang Peng; Fubing Li; Chengyu Zhang; Changshou Hong (Journal of Environmental Radioactivity, 2026)

Quorum sensing in Listeria monocytogenes and control strategies for its inhibition in the food industry - Xinyi Pang; Yunting Wang; Zeyin Feng; Rui Xu; Jing Sun; Xiangfei Li; Yingjian Lu; Hyun-Gyun Yuk (International Journal of Food Microbiology, 2026)

Miocene carbonate crash in the eastern Pacific: A catalyst for early rare earth element enrichment - Yayue Tang; Dengfeng Li; Fei Huang; Rui Wang; Jiewei Hu; Jinzhou Peng; Yu Fu; Xiaoming Sun (Global and Planetary Change, 2026)

Hydration-driven structural engineering via enzymatic glycation: Sustained quercetin release in pullulan-zein coatings for extended walnut preservation - Zi-han Wang; Xue-li Liu; Rui-qi Sun; Bin Qi; Jun-xia Xia; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2026)

Seismic performance of Chinese pavilion-type timber frame with forked column: Experimental tests - Zuoshuai Sun; Hongtai Zhang; Sicheng Li; Rui Zhang; Ping Xiang; Liang-jiu Jia (Engineering Structures, 2026)

Magic chain-flip triboelectric nanogenerator for multi-mode wind and raindrop energy harvesting - Mingxia Chen; Jiahong Yang; Rui Gu; Hai Yan; Zhenghao Li; Siqi Sun; Nuo Xu; Ziwei Huo; Zhong Lin Wang; Qijun Sun; Xiangde Lin (Chemical Engineering Journal, 2026)

Characterization and influencing factors of hydroxymethanesulfonate (HMS) in the North China plain: integration of field measurements and theoretical calculations - Chun Chen; Haijie Zhang; Yele Sun; Junling Li; Zhiqiang Zhang; Jian Gao; Rui Gao; Lianfang Wei; Nan Ma; Wanyun Xu; Pingqing Fu (Atmospheric Environment, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

A unified density-aware network for stored-grain pest detection with intelligent risk assessment - Long Chen; Rui Li; Chengjun Xie; Peng Chen; Jie Zhang; Jianming Du; Hongbo Chen; Runsheng Qi; Jiahui Sun (Journal of Stored Products Research, 2026)

Iron-driven synergism among microbial functional taxa facilitates recovery from denitrification toxicity - Yongzhi Zhang; Xiaoxiao Li; Linjun Gao; Ping Ye; Rui Wang; En Zhou; Tian Sun; Miaoqing Xu; Rui Wan; Xiang Li (Journal of Environmental Management, 2026)

Dietary Haematococcus pluvialis powder enhances the growth and hepatopancreas and intestinal health of Leuciscus waleckii via NF-κB/Nrf2 pathway - Bei Xi; Tong-Tong Tan; Qi Sun; Ming-Xuan Zhang; Jia-Jing Wang; Rui Zhu; Deng-Lai Li; Li-Fang Wu (Fish & Shellfish Immunology, 2026)

Dual-functional La/Fe-MOFs-NH2 for real-time visual removal of fluoride in dynamic environments - Jian Wei; Rui Sun; Han Ma; Junyong He; Dandan Yang; Jiandong Lu; Peidong Hong; Yulian Li; Yahui Li; Chao Xie; Zijian Wu; Lingtao Kong (Chemical Engineering Journal, 2026)

A 45-year high-resolution unstructured wave hindcast for the Australian coast: Validation and climatological insights - Xianghui Dong; Qingxiang Liu; Stefan Zieger; Ian R. Young; Rui Li; Alberto Meucci; Jian Sun; Kejian Wu; Alexander V. Babanin (Coastal Engineering, 2026)

Reconstruction of high-precision gridded precipitation dataset in the alpine cold regions of the Qilian Mountains: An intelligent technological framework from downscaling to calibration - Renjun Wang; Xiang Qin; Yushuo Liu; Jianyu Zhao; Rui Zhang; Zizhen Jin; Yanzhao Li; Wentao Du; Jizu Chen; Weijun Sun (Atmospheric Research, 2026)

Vacuolar K⁺ efflux transporter TaTPK1-5D confers low-K⁺ tolerance of ‘Zhengmai 136’ through interaction with TaCIPK23-4D in bread wheat - Yingna Feng; Qianni Wei; Sisi Sun; Hongbing Zhang; Ting Zhou; Rui Cui; Wenxu Li; Yunqi Liu; Yingpeng Hua; Zhengfu Zhou (Theoretical and Applied Genetics, 2026)

ADAM17 Supports Disinhibition of Pre-sympathetic Glutamatergic Neurons Through Microglial Chemotaxis - Jiawei Wang; Zihan Qiu; Yue Han; Hanxue Wu; Miao Yuan; Yan Liu; Huichao Wang; Shenglan Yuan; Dengfeng Gao; Lina Sun; Xingjuan Chen; Eric Lazartigues; et al. (Neuroscience Bulletin, 2026)

Potential Therapeutic Effects of Astragaloside IV in Parkinson’s Disease Models via Modulation of α-syn-γH2AX-STING-IFN-I Axis - Rui Wang; Fengjiao Sun; Nan Wang; Fang Chen; Xianzhi Wang; Chen Li; Hongcai Wang (Molecular Neurobiology, 2026)